Pendidikan Agama Islam sebagai Sarana Transformasi Nilai-nilai Budaya Islam Modern di Kalangan Generasi Muda - Ahamd Ardiyansyah (Journal Khafi : Journal Of Islamic Studies, 2024)
Islamic Religious Education (IRE) plays a strategic role in transforming the values of modern Islamic culture among the younger generation. This study aims to explore the contributions of IRE in internalizing cultural values that can shape positive character traits in the youth. The method employed in this research is a literature-based approach, where data is collected through an analysis of literature related to the research topic. The findings indicate that key concepts in IRE, such as tolerance, ethics in social life, and the reinforcement of Islamic morals, are capable of changing the behaviors and attitudes of the younger generation toward cultural diversity while also strengthening their morality. The implications of this research highlight the importance of integrating cultural values into the IRE curriculum, which is expected to create individuals who are more adaptive and possess good character in a pluralistic society. This study also recommends further research to explore the long-term effects of religious education on character formation and cultural identity among the younger generation.